2022
DOI: 10.47604/jhmn.1587
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Nurses’ Characteristics and the Nurses’ Attitudes on the Implementation of the Nursing Care Plan in Machakos County

Abstract: Purpose: This descriptive cross-sectional study sought to assess the implementation of the nursing process by nurses in two sub county hospitals in Machakos county, Namely: Kangundo and Kathiani sub county hospitals. The study examined the influence of the nurses’ characteristics and the nurses’ attitudes on the implementation of the nursing process in the  sub County. Methods: A self-administered questionnaire collected quantitative data, while key informant interviews were used to gather qualitative in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Training curriculums for basic nursing cadres in Kenya have incorporated the Nursing Process as the frame work for provision of quality nursing care but unfortunately, Nursing Process is not being adequately utilized in Kenyan hospitals. It was found that nurses who were newly qualified were more familiar with utilization of nursing process when compared with the older nurses (16). Training of nurses into the profession has been challenged by the incongruence between the way nursing process is being taught and being practiced (17).…”
Section: Introductionmentioning
confidence: 99%
“…Training curriculums for basic nursing cadres in Kenya have incorporated the Nursing Process as the frame work for provision of quality nursing care but unfortunately, Nursing Process is not being adequately utilized in Kenyan hospitals. It was found that nurses who were newly qualified were more familiar with utilization of nursing process when compared with the older nurses (16). Training of nurses into the profession has been challenged by the incongruence between the way nursing process is being taught and being practiced (17).…”
Section: Introductionmentioning
confidence: 99%